Bankruptcy design and frictions in Brazil - Andrade, José Matheus Gomes Pessôa (2022)
In the Brazilian bankruptcy process, debtor and creditors bargain to decide whether to liquidate or reorganize the insolvent firm. In January 2021, a Bankruptcy reform came into effect changing the rules of this bargain. Among other points, the reform: forces the liquidation of firms with pending fiscal debts, even those with a reorganization plan already approved by the firm\'s creditors; and ii) prioritizes financing given to firms after they entered judicial reorganization, known in the U.S. literature as DIP financing. We estimate a dynamic bargaining model with asymmetric information and simulate what would happen to a sample of firms in judicial reorganization in Sao Paulo state if the reform was already in effect. Our results indicate that if tax debts are as large as 5% of the total debt, the total recovery rate for in-court reorganization drops 3.3 percentage points. Financing for firms subject to judicial recovery speeds up the resolution of court cases in 1.69 months, while its effects on the total recovery rate for in-court reorganizations range from a 1.96 increase to a 1.92 decrease in the scenarios considered.